NIVELES DE VENTAS EN LA EMPRESA APÍCOLA CASTAÑA DE LA CIUDAD DE BABAHOYO - BANDERAS DOMINGUEZ, KEREN TABITA (2018)
The company "APÍCOLA CASTAÑA" is located in the province of Los Ríos, in the Babahoyo city, is engaged in the production and marketing of products beekeeping (which is obtained thanks to the work done by bees) which are: bee, beeswax, pollen, propolis, royal jelly, currently its owner has 150 beehives each provides about 20 average liters of honey per hive